Decision Paralysis in Uncertainty Higher Education Selection: Transcendental Phenomenology Analysis of Indonesian High School Students - Muhammad Bambang Purwanto; Umar; Evi Agustinasari; Yusri (International Journal of Digital Learning on Languages and Arts, 2025)
This study aims to deeply understand the indecision experienced by 12th-grade high school students in choosing a university, a phenomenon known as decision paralysis. Using a qualitative approach with a transcendental phenomenological method according to Moustakas (1994), this study explored the personal narratives of 20 students attending intensive classes of UN USM PTN at BIMBEL Matrik Palembang City who experienced significant uncertainty in the selection process of majors and higher education institutions. Data were collected through semi-structured in-depth interviews and analyzed through epoch, horizontalization, grouping of meanings, and textural and structural synthesis. The results of the study show three main themes: (1) uncertainty of self-identity and future, (2) external pressure from family, peers, and social media, and (3) coping strategies through personal reflection and decision postponement (gap year). These findings reveal that students' indecision is not just ignorance but the complexity of psychosocial pressures rooted in the dynamics of identity formation and social expectations. This research recommends the need for a personalized approach to career guidance in schools and the importance of systemic support from families and educational institutions in helping students formulate choices that align with their personal potential and values.